Genotype-phenotype relationships in ataxia-telangiectasia and variants. - Gilad, S (1998)
Ataxia-telangiectasia (A-T) is an autosomal recessive disorder characterized by cerebellar degeneration, immunodeficiency, chromosomal instability, radiosensitivity, and cancer predisposition. A-T cells are sensitive to ionizing radiation and radiomimetic chemicals and fail to activate cell-cycle checkpoints after treatment with these agents. The responsible gene, ATM, encodes a large protein kinase with a phosphatidylinositol 3-kinase-like domain. The typical A-T phenotype is caused, in most cases, by null ATM alleles that truncate or severely destabilize the ATM protein. Rare patients with milder manifestations of the clinical or cellular characteristics of the disease have been reported and have been designated "A-T variants." A special variant form of A-T is A-TFresno, which combines a typical A-T phenotype with microcephaly and mental retardation. The possible association of these syndromes with ATM is both important for understanding their molecular basis and essential for counseling and diagnostic purposes. We quantified ATM-protein levels in six A-T variants, and we searched their ATM genes for mutations. Cell lines from these patients exhibited considerable variability in radiosensitivity while showing the typical radioresistant DNA synthesis of A-T cells. Unlike classical A-T patients, these patients exhibited 1%-17% of the normal level of ATM. The underlying ATM genotypes were either homozygous for mutations expected to produce mild phenotypes or compound heterozygotes for a mild and a severe mutation. An A-TFresno cell line was found devoid of the ATM protein and homozygous for a severe ATM mutation. We conclude that certain "A-T variant" phenotypes represent ATM mutations, including some of those without telangiectasia. Our findings extend the range of phenotypes associated with ATM mutations.